1981
DOI: 10.1002/ange.19810930905
|View full text |Cite
|
Sign up to set email alerts
|

Chemie und Biochemie mikrobieller α‐Glucosidasen‐Inhibitoren

Abstract: a-Glucosidasen gehoren zu den wichtigsten Kohlenhydrat-abbauenden Enzymen. Sie katalysieren die Hydrolyse a-glucosidischer Bindungen; ihre Substrate sindj e nach Spezifitat -Oligo-und Polysaccharide. Mikrobielle Inhibitoren von a-Amylasen und anderen intestinalen Kohlenhydrat-abbauenden Enzymen von Saugetieren sind bei der Behandlung von Stoffwechselerkrankungen wie Diabetes mellitus von Interesse. Dariiber hinaus erweitern sie das an strukturellen Variationen uberaus reiche Spektrum der mikrobiellen sekundare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(33 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…A batch ofaplanin (BAY e 4609), containing 20% pseudooligosaccharides of DP 9-14 of the acarbose type (10,36) and 80% non-inhibitory oligosaccharides, was kindly donated by Drs. E. TRUSCHEIT and D. SCHMIDT, Bayer AG, Wuppertal, F.R.G.…”
Section: Methodsmentioning
confidence: 99%
“…A batch ofaplanin (BAY e 4609), containing 20% pseudooligosaccharides of DP 9-14 of the acarbose type (10,36) and 80% non-inhibitory oligosaccharides, was kindly donated by Drs. E. TRUSCHEIT and D. SCHMIDT, Bayer AG, Wuppertal, F.R.G.…”
Section: Methodsmentioning
confidence: 99%
“…Effect of ligands during carbodiimide treatment The accessibility of essential carboxyl groups in glucoamylase was tested by reacting the enzyme with a fixed concentration of EDC and glycine ethyl ester at pH 4.7 in the presence of various specific ligands. The ki,=t values (Table I) reflected the tight-binding inhibitor acarbose (57) to be superior to the substrate maltose as protective agent while both a transition state analoguegluconolactone and a competitive inhibitor maltitol (21, 23) provided marginal protection. The effect of acarbose was concentration-dependent (Fig.…”
Section: Inactivation Of Glucoamylase With Carbodiiinidesmentioning
confidence: 99%
“…Recent work in our laboratory had demonstrated that compounds like conduritol-B-epoxide and Triton X-I00 P/J [17], proved to be similarly ineffective. In contrast, nojirimycin and 1 -deoxynojirimycin were rather potent inhibitors for both trimming glucosidase I and 11. and Nph-x-glucosides ( x --~ x j as substrate Nojirimycin and 1 -deoxynojirimycin are basic glucose analogues, dNM dirrering from nojirimycin by the lack of the anomeric hydroxyl group.…”
Section: Inhibition Studiesmentioning
confidence: 99%